The Strategic Implications of Corporate Responsibility and Sustainability in the UK Banking Sector - Amacanin, Milagros Caminade (2005)
This dissertation is an explorative study of the interface between sustainability and banking. As corporate responsibility has become the buzzword in the banking industry, banks have been urged to actively engage in contributing to sustainable development given their intermediate position in the economic system. The primary research objective of this study is to identify the various facets of the response of banks to sustainability issues. To achieve a more comprehensive understanding of the activities of banks in the UK in the field of sustainability, a multilevel analysis was chosen to cover the industry-wide initiatives and firm-level initiatives towards sustainability through a triangulation of research methods and approaches (desk research, content analysis of published reports, secondary data from existing surveys and case studies). Six high street banks were chosen as subject of study in an attempt to draw an industry mapping of sustainability initiatives. The sustainability issues in the UK banking sector have been shaped and influenced by relevant stakeholders such as the government, competitors and consumers. The competitive structure of the UK banking industry prompted the major banks to strengthen their competitive edge by building up a strong brand and reputation in corporate responsibility. As the UK government seems to be bound to re-regulate the banking sector, banks are prompted be more compliant with government regulations particularly in the aspect of treating the customers fairly. Some of the recurring issues in the financial sector such as financial exclusion, uncompetitive products, low quality of service, financing of projects with questionable social and environmental impact have been emphasised by the government, interest groups and media. The industry-wide sustainability initiatives in the banking sector which aim to lessen or manage sustainability risks in lending and project finance are found to be not effective enough to significantly influence the banks behaviour as the principles are non-binding agreements and banks are bound to self-regulation and self-reporting. The banks which publicly signified their aim to be leaders in the corporate social responsibility field, i.e. HSBC and Barclays, appear to be more pro-active in adopting and promoting the high profile initiatives such as the UN initiative and Equator Principles. However, these high street banks did not signify their support to the London Principles which would entail higher level of sustainability innovations, except for Co-operative Bank which is seen as more advanced in 2 its sustainability goals. The challenge remains in urging the banks to report with quantitative data the outcome of their adoption of these principles. The results of the sustainability assessment of the six banks indicate that majority of the banks have reached the preventive banking phase (Barclays, HBOS, RBS, Lloyds TSB)while only two banks (HSBC and Co-operative Bank) have reached the higher phase of offensive banking. This is consistent with the results of the study of Jeucken (2004) which indicate that most banks in developed countries have exhibited preventive banking as they are bound to follow government regulations to avoid further regulations. Banks are also under pressure from interest groups and media to manage their sustainability risks to avoid reputation damage. Except for Co-operative Bank, it appears that the banks have to aim higher in their sustainability goals and actions as it was found that they still lack product innovations that would stimulate sustainability among customers and society at large. Nonetheless, most banks have generally expressed their commitment to move forward with their sustainability objectives and goals as they are aware of the increasing expectation of their stakeholders and the society at large. It is imperative for banks to be serious in measuring, improving and reporting their sustainability goals and activities as they will eventually be bound to compete on sustainability benchmarking with industry competitors. The government may also need to strengthen its partnership with the banking industry and revisit its regulatory regime in the sector to ascertain the effectiveness of its policy directions in promoting sustainability in the banking sector.